Sustained Release of Amoxicilline Trihydrate for Oral Drug Delivery System - Abdulrhman. A. Akasha (AlQalam Journal of Medical and Applied Sciences, 2017)
Background: Biodegradable macroparticles may develop improved drug delivery system to gastrointestinal tract, for treatment of Helicobacter pylori, included peptic ulcers. Amoxicillin trihydrate macrocapsules have the ability to produce this effect for extended period, were prepared with bees wax as matrix using solvent evaporation techniques, to produce there different 25%, 50% and 75% coating macrocapsules. Macroparticles were examined by optical microscopy and showed spherical shape, The size of particles was determined by using sieve technique and the average size found 350 mm for all batches. IR study was carried out to check the compatibility between the selected polymer (Bees wax) and Amoxicillin Trihydrate. This study was performed to assure that there is complete physical entrapment of the drug into the polymer without any mutual interaction. Methods: Initial in vitro experiments were under taken to examine the degradation rate in phosphate buffer at 37 ºC & PH 5.2 the process was followed up to 8 hours by which 34%, 75% and 25% of particles mass had eroded for 25%, 50% and 75% coating macrocapsules respectively. Results: However the release of amoxicillin trihydrate occurred gradually sustained release 88%, 47% and 50% up to eight hours for 25%, 50% and 75% coating batches, respectively compared to the control of amoxicillin which completely released from the first hour. Conclusion: The macroparticles and control were subjected to microbiological test, the Amoxicillin trihydrate and the three formulation were effective against non-pathogenic bacterial strains of Staphylococcus aureus and E.coli but not effective to more resistance bacteria such as P. aeruginosa.